2021
DOI: 10.1186/s12964-021-00714-1
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus X protein promotes vimentin expression via LIM and SH3 domain protein 1 to facilitate epithelial-mesenchymal transition and hepatocarcinogenesis

Abstract: Background Hepatitis B virus (HBV) X protein (HBX) has been reported to be responsible for the epithelial-mesenchymal transition (EMT) in HBV-related hepatocellular carcinoma (HCC). Vimentin is an EMT-related molecular marker. However, the importance of vimentin in the pathogenesis of HCC mediated by HBX has not been well determined. Methods The expression of vimentin induced by HBX, and the role of LIM and SH3 domain protein 1 (LASP1) in HBX-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…These fusion proteins have been used in combination with untagged vimentin or transfected into vimentin expressing cells in order to study in vivo filament dynamics in live cells [ 40 ], fluorescence recovery after photobleaching [ 43 ] and fluorescence energy transfer to study intermolecular interactions [ 48 ]. Apart from these fluorescent tags, there are non-fluorescent tags such as N-Myc (EQKLISEEDL) [ 49 , 50 ], FLAG (DYKDDDDK) and 3 × FLAG [ 51 , 52 ], HA Tag (YPYDVPDYA) [ 53 ], Spot Tag (PDRVRAVSHWSS) [ 54 , 55 ], V5 Tag (GKPIPNPLLGLDST) [ 56 ] and His Tag (HHHHHH) [ 57 , 58 ]. These are small non-fluorescent peptides, which are fused in frame with the protein of interest so the fusion proteins can be tracked using tag-specific antibodies and therefore they are not suitable for live cell imaging.…”
Section: Discussionmentioning
confidence: 99%
“…These fusion proteins have been used in combination with untagged vimentin or transfected into vimentin expressing cells in order to study in vivo filament dynamics in live cells [ 40 ], fluorescence recovery after photobleaching [ 43 ] and fluorescence energy transfer to study intermolecular interactions [ 48 ]. Apart from these fluorescent tags, there are non-fluorescent tags such as N-Myc (EQKLISEEDL) [ 49 , 50 ], FLAG (DYKDDDDK) and 3 × FLAG [ 51 , 52 ], HA Tag (YPYDVPDYA) [ 53 ], Spot Tag (PDRVRAVSHWSS) [ 54 , 55 ], V5 Tag (GKPIPNPLLGLDST) [ 56 ] and His Tag (HHHHHH) [ 57 , 58 ]. These are small non-fluorescent peptides, which are fused in frame with the protein of interest so the fusion proteins can be tracked using tag-specific antibodies and therefore they are not suitable for live cell imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on STAT3, HBX promotes the expression of HMGB1 to enhance EMT in liver cancer cells ( 121 ). Additionally, our results have shown that HBX can activate STAT3 through LASP1 to facilitate vimentin expression and enhance EMT ( 128 ). Similar to STAT3, STAT5b participates in the induction of EMT mediated by HBX ( 129 ).…”
Section: Role Of Hbx In the Jak-stat Pathwaymentioning
confidence: 81%
“…According to previous reports, the expression of vimentin protein is associated with HBx in HBV-related tumor tissues. The researcher showed that HBx could enhance vimentin expression to facilitate EMT in hepatoma cells [40]. Recently, it has been reported that HBx also regulates the transcription of lncRNAs.…”
Section: Discussionmentioning
confidence: 99%